2019
DOI: 10.1186/s12931-019-1206-8
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette vapour increases virulence and inflammatory potential of respiratory pathogens

Abstract: IntroductionBacteria have been extensively implicated in the development of smoking related diseases, such as COPD, by either direct infection or bacteria-mediated inflammation. In response to the health risks associated with tobacco exposure, the use of electronic cigarettes (e-cigs) has increased. This study compared the effect of e-cig vapour (ECV) and cigarette smoke (CSE) on the virulence and inflammatory potential of key lung pathogens (Haemophilus influenzae, Streptococcus pneumoniae, Staphylococcus aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 54 publications
0
40
1
1
Order By: Relevance
“…Gilpin [87] and Gomez [88] exposed macrophages and several types of bacteria (e.g., influenza, pneumonia) to e-cigarette aerosol extract and found increased bacterial virulence and inflammatory potential as well as decreased bacteria-killing ability. A mouse study [89] found similar effects for macrophages and increased morbidity and mortality among influenza-infected animals, independent of nicotine.…”
Section: Linkages To Immune Function and Susceptibility To Infection mentioning
confidence: 99%
See 2 more Smart Citations
“…Gilpin [87] and Gomez [88] exposed macrophages and several types of bacteria (e.g., influenza, pneumonia) to e-cigarette aerosol extract and found increased bacterial virulence and inflammatory potential as well as decreased bacteria-killing ability. A mouse study [89] found similar effects for macrophages and increased morbidity and mortality among influenza-infected animals, independent of nicotine.…”
Section: Linkages To Immune Function and Susceptibility To Infection mentioning
confidence: 99%
“…Though these studies demonstrated effects of flavorings, some also found significant adverse effects for humectants alone. In several studies [87,88,89,91,92] some effects of e-cigarettes on immune function were less than for cigarettes but some were equal to cigarettes.…”
Section: Linkages To Immune Function and Susceptibility To Infection mentioning
confidence: 99%
See 1 more Smart Citation
“…E-cigarette aerosols are not “safe” and consist of ultrafine particles, nicotine, volatile organic compounds, heavy metals such as nickel, formaldehyde, acrolein and flavorings and chronic inhalation of these harmful chemicals predict negative health impacts [ 21 ]. E-cigarette exposure can enhance the inflammatory profile of viral and bacterial pathogens of the respiratory system and downregulates innate immunity in the lung [ 22 , 23 ]. Since HSPCs are activated in response to injury and infection, it is likely that E-cigarette exposure has a measurable impact on HSPCs.…”
Section: Introductionmentioning
confidence: 99%
“…The two significant predictors of positive IgG results were age ≥60 years and daily vaping. Use of e-cigarettes, both alone and in combination with conventional cigarette smoking, has been associated with increased virulence and inflammatory potential of respiratory pathogens in general [ 25 ] and with COVID-19 in particular [ 26 ]. However, the opposite results were also found for smoking.…”
Section: Discussionmentioning
confidence: 99%